Passive Design Elements Of Traditional And Modern Houses: Case Study On West Coast Of Libya - Abujrad, Abdunnaser Ali Moh (2023)
This study, intended to understand, investigate, and determine the passive design strategies between the traditional courtyard and modern houses in the western coastal region in Libya. Therefore, at the end of this study, this research will propose a general guideline to address the passive design strategies through increasing the passive elements performance for a proper house design. The literature study reviewed the passive design matters, such as house typology, components, elements, and their relations to passive design influences. The methodology applied mixed methods which involved qualitative and quantitative approaches. It adopted the qualitative method to address the case study which was conducted in several phases. Firstly, the data collection was carried out to discover and investigate the chosen cases, including measurements and photographic documentation. Secondly, data processing was performed, which meant a computer generation of things such as AutoCAD drawings, scheduling collected numbers, and clearing photographs. These were needed to prepare the data for the last stage, which was the data analysis and description.